Strengthening Communities through SME Development: A Qualitative Analysis of Management Strategies - Rumasukun, Mohammad Ridwan; Noch, Muhammad Yamin (Manunggal Halim Jaya, 2023)
This research investigates the management strategies employed by Small and Medium-sized Enterprises (SMEs) to strengthen communities and contribute to sustainable growth. The study adopts a qualitative approach, conducting a comprehensive literature review to explore the intricate interplay between SME development and community strengthening efforts. Data collection involves systematic search and retrieval of scholarly articles, books, and reports from academic databases, with a focus on peer-reviewed publications addressing SME management strategies, community development, and relevant theoretical frameworks. Thematic analysis is utilized to identify key themes, patterns, and insights from the literature, shedding light on the role of SMEs in fostering social capital formation, entrepreneurial orientation, and participation in networks. The findings underscore the significant contributions of SMEs to social capital formation within communities through engagement in local networks, participation in community-based initiatives, and commitment to corporate social responsibility (CSR) practices. Additionally, the study highlights the instrumental role of entrepreneurial orientation in driving SME growth and innovation, as well as the importance of SME networks and clusters in facilitating knowledge exchange, collaboration, and collective learning. The research provides theoretical insights into social capital theory, entrepreneurial behavior, and network dynamics, while offering practical implications for SMEs, policymakers, and community stakeholders to promote inclusive growth and socio-economic progress within local communities.